You are on page 1of 2

# FORMULA SSCE 1693

Trigonometric Hyperbolic
cos2
x+ sin2
x=1 ex ex
sinh x =
1 + tan2 x = sec2 x 2
cot2 x + 1 = cosec2 x ex + ex
cosh x =
sin(x y) = sin x cos y cos x sin y 2
cosh2 x sinh2 x = 1
cos(x y) = cos x cos y sin x sin y
1 tanh2 x = sech2 x
tan x tan y coth2 x 1 = cosech2 x
tan(x y) =
1 tan x tan y sinh(x y) = sinh x cosh y cosh x sinh y
sin 2x = 2 sin x cos x cosh(x y) = cosh x cosh y sinh x sinh y
cos 2x = cos2 x sin2 x tanh x tanh y
tanh(x y) =
= 2 cos2 x 1 1 tanh x tanh y
= 1 2 sin2 x sinh 2x = 2 sinh x cosh x
2 tan x cosh 2x = cosh2 x + sinh2 x
tan 2x =
1 tan2 x = 2 cosh2 x 1
2 sin x cos y = sin(x + y) + sin(x y) = 1 + 2 sinh2 x
2 sin x sin y = cos(x + y) + cos(x y) 2 tanh x
tanh 2x =
2 cos x cos y = cos(x + y) + cos(x y) 1 + tanh2 x
Inverse Hyperbolic
Logarithm
sinh1 x = ln(x + x2+ 1), < x <
ax = ex ln a cosh1 x = ln(x 2
+ x 1), x 1
logb x 1 1 1+x
loga x = tanh x = ln , 1 < x < 1
logb a 2 1x

## Differentiations Integrations Differentiations Integrations

d
Z
d
Z
[k] = 0, k dx = kx + C, [sec x] = sec x tan x. sec x tan x dx = sec x + C.
dx dx
k constant. k constant.
d
Z
[cosec x] cosec x cot x dx
d xn+1 dx
Z
[xn ] = nxn1 xn dx = + C, = cosec x cot x. = cosec x + C.
dx n+1
n 6= 1. d
Z
[cosh x] = sinh x. sinh x dx = cosh x + C.
d x
Z dx
[e ] = ex . ex dx = ex + C.
d
Z
dx
[sinh x] = cosh x. cosh x dx = sinh x + C.
dx
d 1
Z
dx
[ln |x|] = . = ln |x| + C.
d
Z
dx x x [tanh x] = sech2 x. sech2 x dx = tanh x + C.
dx
d
Z
[cos x] = sin x. sin x dx = cos x + C. d
Z
dx [coth x] cosech2 x dx = coth x + C.
dx
d
Z = cosech2 x.
[sin x] = cos x. cos x dx = sin x + C.
dx d
Z
[sech x] sech x tanh x dx
d
Z dx
[tan x] = sec2 x. sec2 x dx = tan x + C. = sech x tanh x. = sech x + C.
dx
d
Z
d
Z [cosech x] cosech x coth x dx
[cot x] = cosec2 x. 2
cosec x dx = cot x + C. dx
dx = cosech x coth x. = cosech x + C.
SSCE 1693

## Differentiations of Inverse Functions Integrations Resulting in Inverse Functions

d 1
[sin1 x] = , |x| < 1. Z
dx
dx 1 x2 = sin1 (x) + C.
d 1 1 x2
[cos1 x] = , |x| < 1.
dx 1 x2 Z
dx
d 1 = tan1 (x) + C.
[tan1 x] = . 1 + x2
dx 1 + x2
Z
d 1 dx
[cot1 x] = . = sec1 (x) + C.
dx 1 + x2 |x| x2 1
d 1
[sec1 x] = , |x| > 1.
Z
dx
dx |x| x2 1 = sinh1 (x) + C.
x2 + 1
d 1
[cosec1 x] = , |x| > 1.
dx |x| x2 1
Z
dx
= cosh1 (x) + C, x > 0.
d 1 x2 1
[sinh1 x] = .
dx x2 + 1
1

1+x
Z
d 1 dx
[cosh1 x] = , |x| > 1. = ln + C, |x| < 1.
dx 2
x 1 1 x2 2 1x
d 1
[tanh1 x] = 1

x1
Z
, |x| < 1. dx
dx 1 x2 = ln + C, |x| > 1.
x2 1 2 x+1
d 1
[coth1 x] = , |x| > 1.
dx 1 x2
Z
dx
= sech1 (x) + C, |x| < 1.
d 1 x 1 x2
[sech1 x] = , 0 < x < 1.
dx x 1 x2 Z
dx
d 1 = cosech1 x + C, x 6= 0.
[cosech1 x] = , x 6= 0. |x| 1 + x2
dx |x| 1 + x2